Smells Like Fiscal Policy? Assessing the Potential Effectiveness of the ECB s OMT Program - Timo Wollmershäuser; Nikolay Hristov; Oliver Hülsewig; Thomas Siemsen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper explores the potential effectiveness of the ECB s Outright Monetary Transaction (OMT) program in safeguarding an appropriate monetary policy transmission. Since the program aims at manipulating bank lending rates by conducting sovereign bond purchases on secondary markets, a stable relationship between bank lending rates and government bond rates is of prime importance. Using vector autoregressive models with time varying parameters (TVP VAR) we evaluate the stability of this relationship by focusing on the reaction of bank lending rates to movements in government bond rates over the period 2003 2013. Our results suggest that the potential success of OMTs in restoring the monetary transmission mechanism is limited as the link between bank lending rates and government bond rates has substantially weakened since the end of 2008.
Keywords: E42; E43; E58; 330